Biologically active additives (baa) for energy generation in ice hockey - Gavrilova, E. A.; Churganov, O. A.; Yakovlev, Yu. V.; Kuznetsov, P. K. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze benefits of modern biologically active additives for energy generation mechanisms in the ice hockey sport.